RARE CLINICAL CASE OF ENDOMETRIOSIS OF ROUND LIGAMENT OF THE UTERUS - E. G. Drandrova; M. E. Shchepelev; E. V. Moskvichev; T. Yu. Leont’eva; I. V. Tsyrlina (Акушерство, гинекология и репродукция, 2017)
Endometriosis of the round ligament of the uterus is a rare clinical pathology, that is difficult for differential diagnostics. Clinical case of the endometriosis of the round ligament of the uterus is described. Issues of etiology and pathogenesis of inguinal endometriosis are mentioned. Modern views about diagnostics and treatment of endometriosis are described. Mapping of data of gynaecological anamnesis, complaints with the results of laboratory and instrumental research methods allows put correct preoperational diagnosis and decrease time from the first visit of doctor up to operative treatment.